PENGEMBANGAN MODUL AJAR MATEMATIKA MATERI PECAHAN KELAS IV DI SEKOLAH DASAR - Iqnatia Alfiansyah (COLLASE (Creative of Learning Students Elementary Education), 2021)
AbstractBased on the results of interviews and observations, several problems were found, namely the lack of students 'understanding of the mathematics subject matter of fractions and the textbooks used did not facilitate students' thinking processes. This study aims to develop a mathematics teaching module for grade IV fractions in elementary schools. This development research uses three stages of the 4-D model which includes define, design, and develop with the modification of the researcher. The subjects of this study were 14 grade students of SD Negeri Iker-Iker Geger Cerme Gresik. The data collection methods used were validation, student response questionnaires, and learning outcomes tests. Based on the results of data analysis, the results of validation and testing, it was found that the development of mathematics teaching modules for grade IV fraction material in elementary schools resulted in quality teaching modules, namely a) teaching modules categorized as very valid (86.25), b) teaching modules categorized as practical with little revision, c) the teaching module is categorized as effective with a classical completeness percentage of 85.71% and a questionnaire score percentage of students' responses to 88.57%.